80 Impacting the quality of care in severe aortic stenosis using facilitated data transfer – delay to intervention in the UK versus other european countries (impulse registry). (June 2018) - Steeds, Rick; Thambyraja, Jeetandra; Lloyd, Guy; Lutz, Matthias; Rudolph, Tanja; Kurucova, Jana; Bramlage, Peter; Frey, Norbert; Messika-Zeitoun, David
Abstract : Introduction: Many patients with severe AS are inappropriately denied intervention and continue to present late with advanced symptoms. IMPULSE is a prospective, multicentre registry conduced in 23 centres across 9 European countries, investigating the efficacy of facilitated data transfer (FDT) in improving time to intervention in severe AS. Results from the 3 large UK centres were compared to those of other large centres in the rest of Europe. Methods : Hospitals with all treatment options (sAVR, TAVI, BAV) on site were asked to document, over a 1 year period, patients with severe AS that presented with or without symptoms. A 3 months purely observational phase A was followed by a 6 months interventional phase (FDT), and a 3 months observational phase B to investigate a legacy effect. Results: A total of 2171 pts were enrolled of which 515 were recruited in the UK. Patients in the UK had a mean age of 78.1±11.0 years, 46.8% were female, the mean log EuroScore I was 17.1±13.3 and 77.9% of the patients were considered symptomatic based on the presence of chest pain, shortness of breath, dizziness on exertion. These baseline characteristics did not differ between the UK and the rest of Europe. Concomitant valve disease aortic (17.4 vs 5.1%), mitral (18.6 vs 8.3%) and tricuspid (16.2 vs 5.3%) regurgitation was more frequently diagnosed in the UK than the rest of Europe (all p<0.001). Treatment options chosen differed substantially between the UK and the rest of Europe in that less TAVI decisions (29.9 vs 49.7%, p<0.001), and more decisions for non-invasive treatment options (BAV, Medical Management, Watchful Waiting) were made (48.3 vs 25.6%, p<0.001) while the proportions of patients assigned for surgery were about the same (21.8 vs 24.7%, p=0.188). Furthermore there was a lower proportion of patients receiving TAVI (17.8 vs 44.3%, p<0.001) and SAVR (11.3 vs 20.4%) within three months after the decision was made (p<0.001). FTD increased the proportion of patients undergoing either TAVI or SAVR in the overall cohort, with the difference remaining significantly different between the UK (36.0%) vs the rest of Europe (64.3%, p<0.001). While there was a shortening of the time to intervention in the TAVI group with FTD, there was no shortening observed in the SAVR group, the difference between the UK and the rest of Europe being statistically significant in all phases. Conclusions: Management practices differ in the UK compared to Europe in patients with severe AS, with more frequent selection of watchful waiting and medical management. FTD increased the number of patients going for intervention, although rates remained low given that the study recruited only patients with severe aortic stenosis confirmed on echo and almost 4/5ths were symptomatic. In addition, there is a significant delay in the UK compared to Europe between decision making and actual performance of TAVI.